Gari: mechanization to improve sales - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Gari is the dry, toasted flour produced from cassava after laborious processing. In this form i tis a convenience food which is particularly popular in Togo and neighbouring countries. None the less gari is not profitable for the women who make it....